The prohibition of reckless credit granting as a measure to achieve a responsible lending regime : focus on pre-agreement assessment - Van Heerden, C.M. (Corlia) (University of Pretoria, 2017)
Mini Dissertation (LLM)--University of Pretoria, 2016.